(3GdETGQI Edi Yde GdYHGQIs - (3eMeO Hf CMeO Hf YeQ, CHh YHO Gddg GdSGdej,J (B800 (3g` s
(3ChdgG (B:s
(3GdMeO ddg NGdb GdCQhGM haGdb GdCUHGMdeG UGQJ YHGQI GdQDjG TQjag MdGdgG s
(3BNQgG (B:s
(3hfXQJ ai GdUbQ aGPG gh WGFQ YQHi djS ef WjhQ GdCYGLe ade CQ ai GdYQH CUbQ ef GdMLGL Hf jhSa s
(3eQJH Ydi NeSjf HGHGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B329 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B304s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B121 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3165(3)) s
Keywords: (3JYHjQ GdQDjGs